Prosumer Centric Strategy for Utilization of EV in Microgrid - Sri Lakshmi E.; Singh S.P. (My University, 2025)
The paper explores the optimization of microgrid operation with solar energy, energy Storage System, and electric vehicles as additional support to the grid. It introduces bidirectional power flow strategies to utilize Electric vehicle (EV) energy for both home and grid power, regulated by managing the rate of charge/discharge. The proposed strategy considers EV availability, transformer loading, and day-ahead prices. Using Markov model with factual hourly vehicle usage data, the paper predicts EV availability. Its primary objective is to minimize the operational costs for prosumers while minimizing battery degradation. The paper formulates schedule and battery degradation of EV/ESS as a mixed-integer problem, solved using Mixed Integer Linear Programming (MILP) with IBM CPLEX optimizer. Furthermore, the paper also introduces incentive pricing strategy to boost EV participation in energy transactions and reduce grid dependency. © 2024 IEEE.